Bank credit and market-based finance for corporations: The effects of minibond issuances - Steven Ongena; Sara Pinoli; Paola Rossi; Alessandro Diego Scopelliti (European Central Bank (ECB), 2020)
We study the effects of the diversification of funding sources on the financing conditions for firms. We exploit a regulatory reform which took place in Italy in 2012, i.e., the introduction of "minibonds", which opened a new market-based funding opportunity for unlisted firms. Using the Italian Credit Register, we investigate the impact of minibond issuance on bank credit conditions for issuer firms, both at the firm-bank and firm level. We compare new loans granted to issuer firms with new loans concurrently granted to similar non-issuer firms. We find that issuer firms obtain lower interest rates on bank loans of the same maturity than non-issuer firms, suggesting an improvement in their bargaining power with banks. In addition, issuer firms reduce the amount of used bank credit but increase the overall amount of available external funds, pointing to a substitution with bank credit and to a diversification of corporate funding sources. Studying their ex-post performance, we find that issuer firms expand their total assets and fixed assets, and also raise their leverage.
Keywords: G21; G23; G32; G38; 330; bank credit; capital markets; minibonds; loan pricing; SME finance